2016
DOI: 10.3390/agriculture6030035
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of Herbivores Consuming Phytoestrogen-containing Medicago and Trifolium Species

Abstract: Despite their unrivalled value in livestock systems, certain temperate, pasture, legume species and varieties may contain phytoestrogens which can lower flock/herd fertility. Such compounds, whose chemical structure and biological activity resembles that of estradiol-17α, include the isoflavones that have caused devastating effects (some of them permanent) on the fertility of many Australian sheep flocks. While the persistence of old 'oestrogenic' ecotypes of subterranean clover (Trifolium subterraneum) in pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 106 publications
(128 reference statements)
1
60
0
1
Order By: Relevance
“…In addition, the focus of these studies was to provide advice for sheep production systems. Further research to determine the response of cattle reproductive performance to coumestrol would be of benefit, both to corroborate with the studies described in Reed (2016), and to provide an indication of the coumestrol level that may be a risk to cattle fertility. Across the experiments in this study a range of alfalfa stand ages were used, however this was often in different months or years and so they cannot be compared.…”
Section: Development Stagementioning
confidence: 70%
See 1 more Smart Citation
“…In addition, the focus of these studies was to provide advice for sheep production systems. Further research to determine the response of cattle reproductive performance to coumestrol would be of benefit, both to corroborate with the studies described in Reed (2016), and to provide an indication of the coumestrol level that may be a risk to cattle fertility. Across the experiments in this study a range of alfalfa stand ages were used, however this was often in different months or years and so they cannot be compared.…”
Section: Development Stagementioning
confidence: 70%
“…Most research has been conducted on the effect of coumestrol on sheep. However, as detailed in a review by Reed (2016), a few studies have also reported impaired fertility in cattle.…”
mentioning
confidence: 99%
“…A strong association between formononetin intake and equol concentration in plasma was demonstrated, so that cows' milk can be considered as a source of equol in human nutrition [20][21][22][23][24][25]. On the other hand, consumption of forages with high concentrations of formononetin and coumestrol has shown to cause temporary or permanent reproductive problems in some ruminants, mostly in sheep and cattle [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…They also cause haemolysis of red blood cells and are toxic to rats [32]. Saponins from Bulbostermmapaniculatum and Pentapamax leschenaultii have alsobeen demonstrated to have anti-spermal effects on human spermatozoa [33]. They significantly inhibited acrosine activity of human sperms and the spermicidal effect was attributed to strong damage of the spermal plasma membrane [34].…”
Section: Biochemical Effects Of the Anti-nutritional Factorsmentioning
confidence: 99%